(untitled) (CIPEEX, 2022)
NOWADAYS, AMONG ALL THE DIFFICULTIES THAT EDUCATION IN BRAZIL GOES THROUGH, THERE IS A GREAT LACKOF INTEREST ON THE PART OF MANY STUDENTS, FOR ANY SCHOOL ACTIVITY. FOR KUPFER (1995, P. 79), €Œ...THE LEARNING PROCESS DEPENDS ON THE REASON THAT MOTIVATES THE SEARCH FOR KNOWLEDGE€,HIGHLIGHTING THE REASON FOR ITS IMPORTANCE. THEREFORE, THE PRESENT WORK PRESENTS THE PROCESSCARRIED OUT FOR THE CONSTRUCTION OF ONE OF THE MODULES OF THE €ŒUNICASH€ APPLICATION, WHICHAIMS TO ENCOURAGE THE STUDENT TO PERFORM ACTIVITIES THAT WILL BRING BENEFITS. THE APPLICATION WASDESIGNED LOOKING TO ATTEND THE STUDENTS OF THE EVANGELICAL UNIVERSITY OF ANÁPOLIS, TO TRANSFORMEACH ACTIVITY PERFORMED INTO A SCORE, WHERE THE STUDENT CAN EXCHANGE FOR CONSUMABLE ITEMS.FOR THE CONSTRUCTION OF THE MVP, AGILE METHODOLOGIES WERE USED THAT ARE BASED ON RESEARCHAND REQUIREMENTS GATHERING IN SHORT CYCLES, TO ADD VALUE TO THE PRODUCT. IN PRODUCT DESIGN, LEANINCEPTION WAS USED FOR BUSINESS ALIGNMENT AND REQUIREMENTS GATHERING, AND IN DEVELOPMENT,SCRUM WAS USED TO FACILITATE PROJECT MANAGEMENT, WITH THE CONSTRUCTION OF THE BACKLOG ANDMONITORING OF THE STEPS OF THE DOWNSTREAM FLOW, INVOLVING ALL FRONTS OF WORK SUCH AS DESIGN, APIDEVELOPMENT, SCREEN BUILDING AND TESTING. AT THE END OF THESE STAGES OF PROJECT DEVELOPMENT,THE FLOW OF USE OF THE POINTS ACQUIRED BY THE STUDENT WAS OBTAINED, WITH AN INTERFACE IN USABILITYATTRIBUTES FOLLOWING THE PRINCIPLES OF JAKOB NIELSEN. IT IS WORTH MENTIONING THAT THIS ARTICLE SEEKSTO POINT WAYS TO THOSE INTERESTED IN KNOWING HOW THE PROCESS OF PLANNING AND ELABORATION OF ASOFTWARE APPLICATION HAPPENS. FINALLY, THE PRESENT WORK POINTED OUT WAYS FOR A POSSIBLE SOLUTIONTO THE LACK OF MOTIVATION OF STUDENTS, HIGHLIGHTING THE EXCHANGE OF EFFORT IN BENEFITS.